The Role of Educational Innovation in Learning - Muchimapiro, Vachirasake (Ratchaphruek Journal, 2014)
An innovation means a new thing or a new method of doing something. Thus, a new education material and a new education method are called “the educational innovation”. The educational innovation comes from creativity and can be divided into two main types. They are the education method and the education media. Instructors use these educational innovations in developing students’ learning process into three levels, which are perception level, comprehension level and transformation level. The objective of this article is to encourage instructors in creating educational innovations continually in order to accomplish the learning goal in developing students to be intelligent, good, and happy citizens.